A switch point in the molecular chaperone Hsp90 responding to client interaction - Daniel Andreas Rutz (Nature Portfolio, 2018)
The heat shock protein 90 (Hsp90) chaperone undergoes large conformational changes during its functional cycle. Here the authors combine in vivo, biochemical, biophysical and computational approaches and provide insights into the allosteric regulation of Hsp90 by identifying and characterizing a switch point in the Hsp90 middle domain.